Improving Students’ Vocabulary Mastery by Using English Songs to The Tenth Grade Students of SMA Dharma Wanita Medan - Resi Niyati Pardede; Novalina Sembiring; Fiber Yun A Ginting (Verba: Journal of Applied Linguistics, 2023)
The aims of this study are to prove whether using English songs can improve students vocabulary mastery and to know the students responses after being taught by using English songs. This research is Classroom Action Research (CAR) which was conducted by using English songs to the tenth grade students of SMA dharma Wanita Medan in the Academic Year 2022/2023. The quantitative data analysis showed that the students mean score increased continuously from 61 in pre-test, 68 in formative test, and 79 in post-test. The qualitative data analysis showed that the students' responses after being taught by using English songs are very good. It can be seen from observation sheets and field notes, they felt more enthusiastic and motivated to learn vocabulary mastery after English songs was applied. The percentage of students who strongly agree is 61 (61%), agree is 39 (39%), strongly disagree is 0 (0%). Using English songs beneficial and effective for teaching vocabulary mastery. It is suggested that English teacher using English songs as an alternative in teaching vocabulary mastery to the students in Senior High School in order to improve their achievement.